EFFECTS OF STORMINESS, SAND SUPPLY AND THE NORTH ATLANTIC OSCILLATION ON SAND INVASION AND COASTAL DUNE ACCRETION IN WESTERN PORTUGAL - Clarke M.L.; Rendell H.M. (My University, 2006)
Holocene forested coastal dunes fringe the Atlantic coast of western Portugal. Mapping of dunes in the field and using air photographs shows a range of forms reflecting dominant northwest and westerly onshore wind regimes. Planting of maritime pine forests in the thirteenth and twentieth centuries was initiated because of sand invasion causing problems for human settlement and agriculture. Early Holocene dunes have a well-developed podsol and date to 9.7 and 8.2 ka, suggesting at least some of these sands may have been emplaced during a global cooling event. Significant transgressive dune accretion at 2.2 and 1.5 ka, implies abundant sand supply and strong onshore winds The most recent dune-building period dates to AD 1770-1905 and coincides with a predominantly negative winter North Atlantic Oscillation index (NAOi). Accretion of dunes along the Portuguese coast appears out of phase with dune development in southwest France, which may reflect different Atlantic storm tracks driven by changes in the dominance and state of the NAOi.
Keywords: SAND INVASION; NORTH ATLANTIC STORMINESS; NORTH ATLANTIC OSCILLATION; LUMINESCENCE DATING; HOLOCENE; PORTUGAL; DUNES; AEOLIAN ACCRETION; COASTAL PROCESSES; Cenozoic::Quaternary::Holocene; Кайнозой::Четвертичная::Голоцен